ЮПҚА ПАРДАЛИ ГЕТЕРОСТРУКТУРАГА АСОСЛАНГАН ҚУЁШ ФОТОЭЛЕМЕНТЛАРИНИНГ АСОСИЙ ФИЗИКАВИЙ ПАРАМЕТРЛАРИНИ АНИҚЛАШ - Тошпулатова, Д.Х. (SCIENCE and SOCIETY, 2021)
The article deals with comparative analysis of existing to date thinly pellicle technologies for transformation of sunny energy to electric power is conducted. Basic features over technology of production are brought on the basis of amorphous and microcrystalline silicon of sunny elements, providing them competitive edges.
Keywords: power engineering specialist of a sun sources; proceeded in energy; electric energy; sunny element; mono crystalline and poly crystalline silicon; thin tape; amorphous silicon; sunny module